(untitled) (8gen-ART, 2022)
The aim of this study is to analyze and compile the fundamental changes in interior architecture design from the beginning of the new millennium to the present. In this context, a literature study was conducted and visuals related to the subject were used. In the face of the socio-cultural, socio-political and socio-economic effects brought about by the new millennium, the basic principles of interior design approach have been preserved, while various new understandings have emerged on the physical and virtual fundamentals. While Interior Architecture is a branch of art and science that creates a route on the living axis, artificial intelligence has begun to be added to this axis by users. The staff of the Henn Na Hotel chain in Japan consists of artificial intelligence. The pandemic era, the rate of advancement of technology and globalization are among the main developments affecting this process. The rapid development of technology has allowed interior spaces to be considered as virtual spaces as shells and the rise of smart interiors. Interiors have started to communicate with it’s user and interactive spaces have also occured. Fictional spaces have entered a perceptual-conceptual development phase thanks to effects and sound technologies. Detailed and accurate evaluation of this process is important in terms of predicting the future and new trends.